2017
DOI: 10.1037/emo0000275
|View full text |Cite
|
Sign up to set email alerts
|

Maternal anxiety predicts attentional bias towards threat in infancy.

Abstract: Although cognitive theories of psychopathology suggest that attention bias towards threat plays a role in the etiology and maintenance of anxiety, there is relatively little evidence regarding individual differences in the earliest development of attention bias towards threat. The current study examines attention bias towards threat during its potential first emergence by evaluating the relations between attention bias and known risk factors of anxiety (i.e., temperamental negative affect and maternal anxiety)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
99
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 101 publications
(113 citation statements)
references
References 88 publications
(146 reference statements)
7
99
6
Order By: Relevance
“…A strong line of studies has examined the emergence of differential attention to, and processing of, emotion stimuli, particularly as linked to threat processing (Peltola et al, 2015; Peltola et al, 2013; Peltola, Leppanen, Maki, et al, 2009; Peltola et al, 2008; Peltola, Leppanen, Vogel-Farley, et al, 2009). This literature has focused almost exclusively on normative changes over time (but see Forssman et al, 2014; Morales et al, in press; Peltola et al, 2015; Ravicz et al, 2015). In parallel, the anxiety literature has examined individual differences in threat processing as a putative causal mechanism for the emergence of social maladjustment and disorder (Dudeney et al, 2015; Pergamin-Hight, Naim, Bakermans-Kranenburg, van IJzendoorn, & Bar-Haim, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A strong line of studies has examined the emergence of differential attention to, and processing of, emotion stimuli, particularly as linked to threat processing (Peltola et al, 2015; Peltola et al, 2013; Peltola, Leppanen, Maki, et al, 2009; Peltola et al, 2008; Peltola, Leppanen, Vogel-Farley, et al, 2009). This literature has focused almost exclusively on normative changes over time (but see Forssman et al, 2014; Morales et al, in press; Peltola et al, 2015; Ravicz et al, 2015). In parallel, the anxiety literature has examined individual differences in threat processing as a putative causal mechanism for the emergence of social maladjustment and disorder (Dudeney et al, 2015; Pergamin-Hight, Naim, Bakermans-Kranenburg, van IJzendoorn, & Bar-Haim, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, we were able to derive effect size estimates from recent papers examining main-effects and two-way interactions in infant eye-tracking studies of attention to threat (LoBue, Buss, Taber-Thomas, & Pérez-Edgar, 2017; Morales et al, in press). These studies found medium effect sizes ( d 's between 0.37 and 0.42) for the comparable analyses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Morales et al. () reported an association between maternal current anxiety symptoms and infant's heightened bias to angry facial expressions. This hypersensitivity of the infant's developing threat‐appraisal system may increase vulnerability to environmental stressors.…”
Section: The Present Studymentioning
confidence: 93%
“…Farley, Hietanen, & Nelson, 2009), but there are indications that this tendency may decline and shift toward a more adult-like (e.g.,Green, Williams, & Davidson, 2003) distributed scanning pattern over time.Further research is needed to examine whether some of these processes contribute to infants' attention holding on faces (and, particularly, fearful faces) and the potential subsequent reduction of these biases in early childhood. WhileNakagawa and Sukigara (2012) observed in a small longitudinal sample that attention to neutral, happy, and fearful faces declined from 24 to 36 months of age, cross-sectional studies investigating attention to neutral, happy, and angry faces in 4-to 24-month-old(Morales et al, 2017) and 9-to 48-month-old (Burris, Barry-Anwar, & Rivera, 2017) children pointed to a more stable pattern by showing that the patterns of attention biases toward angry and happy faces were not affected by age. WhileNakagawa and Sukigara (2012) observed in a small longitudinal sample that attention to neutral, happy, and fearful faces declined from 24 to 36 months of age, cross-sectional studies investigating attention to neutral, happy, and angry faces in 4-to 24-month-old(Morales et al, 2017) and 9-to 48-month-old (Burris, Barry-Anwar, & Rivera, 2017) children pointed to a more stable pattern by showing that the patterns of attention biases toward angry and happy faces were not affected by age.…”
mentioning
confidence: 96%